Security Price Changes and Transaction Volumes: Some Additional Evidence - Epps, Thomas W. (Journal of Financial and Quantitative Analysis, 1977)
In an earlier paper [1] a model of securities markets was introduced which implies that the ratio of transaction volume to price change is greater for transactions on which price rises than for those on which price falls. Examination of individual transactions data for a sample of corporate bonds showed that price changes and transaction volumes for those securities appears to behave in a manner consistent with the theory. However, the paper raised the question of whether the same is true for stocks. The positive dependence on share price of broker commissions for stocks could easily eliminate, or even reverse the sign of, the predicted positive difference between the absolute values of slopes of buyers' and sellers' reservation demand functions; and it is this difference which leads the model to predict the inequality of the ratios of volume to price change on upticks and downticks. This note records the results of tests of the model with stock data, using volumes and price changes pertaining both to individual transactions and to trading days. The tests indicate that the ratios of volume to price change exhibit the predicted relationship, when one of the two possible measures of volume is employed.